DEVELOPMENT AND EVALUATE ADVANTAGES OVER TRADITIONAL AGRICULTURE OF A HYDROPONIC SYSTEM (International Journal of Food and Nutritional Sciences, 2023)
Hydroponics, a method of cultivating plants without soil, offers numerous advantages over traditional agriculture, including increased yield, reduced water usage, and minimized environmental impact. This research paper explores the design and development of a hydroponic system, focusing on key considerations such as system type, nutrient solution preparation, environmental control, and plant selection. The paper also discusses the potential benefits and challenges of hydroponic systems, along with future research directions in this field.